Top-Down and Bottom-Up Controls on Microeukaryotic Diversity (i.e., Amplicon Analyses of SAR Lineages) and Function (i.e., Metatranscriptome Analyses) Assessed in Microcosm Experiments - Grattepanche, Jean-David; Katz, Laura A. (Frontiers in Marine Science, 2020)
The availability of high-throughput sequencing (HTS) has transformed our understanding of the diversity of microbial eukaryotes (i.e. protists) across diverse habitats. Yet relating this biodiversity to function remains a challenge, particularly in the context of microbial food webs. Here we perform a set of microcosm experiments to evaluate the impact of changing predator and prey concentrations on a marine protist community, focusing on SAR (Stramenopila, Alveolata, and Rhizaria) lineages. We combine an estimate of taxonomic diversity through analysis of SSU-rDNA amplicons with metatranscriptomics, a proxy for function. We assess changes in a community sampled from New England waters with varying concentrations of predators (copepods) and prey (phytoplankton less than 15µm in size). The greatest impact observed is on the diversity and function of the small plankton (2-10µm) community in the presence of high prey abundance (i.e. bloom conditions). Many SAR taxa in the nanosized fraction decrease with increasing phytoplankton abundance, while ciliates (from both nano- and microsized fraction) increase. A large number of transcripts and function estimates in the nanoplankton are downregulated during our simulated phytoplankton bloom. We also find evidence of an interaction between increasing phytoplankton and copepods on the microsized planktonic community, consistent with the hypothesis that phytoplankton and copepods exert bottom-up control and top-down control on the microsized protists, respectively. Together our analyses suggest community function (i.e. diversity of gene families) remains relatively stable, while the function at the species level (i.e. transcript diversity within gene families) show a substantial reduction of function under bloom conditions. Our study demonstrated that interactions within plankton food webs are complex, and that the relationships between diversity and function for marine microeukaryotes remain poorly understood.